2022
DOI: 10.1186/s40001-022-00637-8
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of using intravenous immunoglobulin (IVIG) in critically ill COVID-19 patients’: a retrospective, multi-centric cohort study

Abstract: Background During the COVID-19 pandemic, different treatments have been used in critically ill patients. Using intravenous immunoglobulin (IVIG) has been suggested in various studies as an effective option. Our study aims to access the efficacy of IVIG in critically ill COVID-19 patients. Methods In this retrospective matched cohort study, records of three tertiary centers with a large number of COVID-19 admissions were evaluated and used. Based on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…After screening, 17 studies (including five RCT ( 18 , 19 , 22 , 41 , 42 ) and 12 cohort studies ( 20 , 21 , 43 52 ) that were considered to meet the selection criteria and included in the meta-analysis. Different form the latest study ( 28 ), four studies were newly identified and included in this meta-analysis ( 48 50 , 52 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening, 17 studies (including five RCT ( 18 , 19 , 22 , 41 , 42 ) and 12 cohort studies ( 20 , 21 , 43 52 ) that were considered to meet the selection criteria and included in the meta-analysis. Different form the latest study ( 28 ), four studies were newly identified and included in this meta-analysis ( 48 50 , 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Effects of IVIg on the need for mechanical ventilation were reported in eight studies, including three RCT studies ( 19 , 41 , 42 ) (RR= 0.77 [0.49, 1.21], P = 0.26; I 2 = 39%) and five cohort studies ( 21 , 44 , 46 , 48 , 50 ) (RR= 1.02 [0.76, 1.37], P = 0.89; I 2 = 66%) ( Figure S3 ). One RCT study was excluded in this analysis because all patients had applied mechanical ventilation before allocating to receive IVIg treatment ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a retrospective, multicenter cohort study assessing the outcome of IVIG in critically ill COVID-19 patients found no remarkable differences in hospitalization, ICU length of stay, duration of mechanical ventilation, and even mortality rate [ 40 ]. A multicenter, double-blinded, placebo-controlled, and phase 3 trial involving moderate-to-severe COVID-19 ARDS showed that IVIG did not improve clinical outcomes at Day 28 and showed an insignificant increase in adverse events [ 41 ].…”
Section: Discussionmentioning
confidence: 99%